Risk Factors for Severe Hand-Foot-Mouth Disease in China: A Systematic Review and Meta-Analysis - Li, Peiqing; Huang, Yuge; Zhu, Danping; Yang, Sida; Hu, Dandan (Frontiers in Pediatrics, 2021)
Background: This study aimed to identify potential risk factors for severe hand-foot-mouth disease (HFMD). Methods: The PubMed, Embase, the Cochrane Library, Sinomed, WanFang, CNKI, and VIP databases were searched (up to August 2021). Results: Twenty-nine studies (9241 and 927,355 patients with severe HFMD and controls, respectively; all from China) were included. EV71 was associated with higher odds of severe HFMD compared with other agents (OR=4.44, 95%CI: 3.12-6.33, p<0.001). Being home-raised (OR=1.99, 95%CI: 1.59-2.50, p<0.001), higher number of children in the family (OR=2.09, 95%CI: 1.93-2.27, p<0.001), poor hand hygiene (OR=2.74, 95%CI: 1.78-4.23, p<0.001), and no breastfeeding (OR=2.01, 95%CI: 1.45-2.79, p<0.001) were risk factors for severe HFMD. First consulting to a district-level or above hospital (OR=0.34, 95%CI: 0.25-0.45, p<0.001) and diagnosis of HFMD at baseline (OR=0.17, 95%CI: 0.13-0.24, p<0.001) were protective factors against severe HFMD. Fever, long fever duration, vomiting, lethargy, leukocytosis, tic, and convulsions were each associated with severe HFMD (all p<0.05), while rash was not. Conclusions: EV71, lifestyle habits, frequent hospital visits, and symptoms are risk factors for severe HFMD in children in China, while early diagnosis and admission to higher-level hospitals are protective factors.